The Impact of a National Tobacco Education Campaign on State-Specific Quitline Calls. Issue 5 (May 2016) - Zhang, Lei; Malarcher, Ann; Babb, Steve; Mann, Nathan; Davis, Kevin; Campbell, Kelsey; Schauer, Gillian; Alexander, Robert; Debrot, Karen; Rodes, Robert
Purpose: The ads from the first federally funded national tobacco education campaign, Tips From Former Smokers (Tips), considerably increased quitline calls nationwide. This study evaluates the effect of Tips on state-specific quitline calls. Design: Precampaign, during-campaign, and postcampaign comparison; regression modeling. Setting: All fifty states as well as the District of Columbia. Subjects: Calls to state quitlines. Intervention: Tips. Measures: Tips campaign exposure was measured by gross rating points (GRPs). Calls to quitline's 1-800-QUIT-NOW were assigned to markets in each state based on their area codes. Analysis: Multivariate regression was used to assess the relationship between calls to state quitlines and media market-level Tips GRPs, while controlling for market and area code characteristics. Results: Nationally, every 100 Tips GRPs per week at the market level was associated with an average of 45 additional quitline calls in each area code (β = 44.65, p < .001). Tips GRPs were associated with significant increases in quitline calls in 46 states and the District of Columbia, of which 11 experienced effects significantly larger than the national average and 5 experienced significantly smaller effects. We were unable to detect statistically significant effects of GRPs on call volumes for four states. Graphically, call volumes in those states followed Tips GRPs. Conclusion: The Tips campaign significantly increased calls to quitlines for almost all the states. These findings underscore the effectiveness of national tobacco media campaigns for reaching state audiences.